Effect of 475°C embrittlement on the low cycle fatigue behaviour of lean duplex stainless steels - Strubbia, Renata (2018)
Lean duplex stainless steels (LDSSs) with lower nickel and molybdenum are less susceptible to suffer spinodal decomposition than standard duplex stainless steels. It is the purpose of this work to study the effect of thermal embrittlement on the low cycle fatigue behaviour of 2 LDSSs with different Creq and Nieq. The correlation between the fatigue behaviour and the dislocation structure is attempted. Transmission electron microscopy was used to observe the dislocation microstructure. Additionally, STEM-EDS technique in conjunction with Vickers microhardness measurements was used to characterize the amplitude of the spinodal decomposition. The results show that the LDSS with lower Creq and Nieq values exhibits improved fatigue properties in the as received and aged conditions. Furthermore, it is important to emphasize that with an adequate volume fraction of phases in LDSSs, the ageing treatment leads to an increase in strength without causing a great detriment in low cycle fatigue life.